Histological chorioamnionitis shapes the neonatal transcriptomic immune response. (July 2016) - Weitkamp, Jörn-Hendrik; Guthrie, Scott O.; Wong, Hector R.; Moldawer, Lyle L.; Baker, Henry V.; Wynn, James L.
Abstract: Background: Histologic chorioamnionitis (HCA) is commonly associated with preterm birth and deleterious post-natal outcomes including sepsis and necrotizing enterocolitis. Transcriptomic analysis has been used to uncover gene signatures that permit diagnosis and prognostication, show new therapeutic targets, and reveal mechanisms that underlie differential outcomes with other complex disease states in neonates such as sepsis. Aims: To define the transcriptomic and inflammatory protein response in peripheral blood among infants with exposure to histologic chorioamnionitis. Study design: Prospective, observational study. Subjects: Uninfected preterm neonates retrospectively categorized based on placental pathology with no HCA exposure ( n = 18) or HCA exposure ( n = 15). Outcomes measures: We measured the transcriptomic and inflammatory mediator response in prospectively collected whole blood. Results: We found 488 significant ( p < 0.001), differentially expressed genes in whole blood samples among uninfected neonates with HCA exposure that collectively represented activated innate and adaptive immune cellular pathways and revealed a potential regulatory role for the pleotropic microRNA molecule miR-155. Differentially secreted plasma cytokines in patients with HCA exposure compared to patients without HCA included MCP-1, MPO, and MMP-9 ( p < 0.05). Conclusions: Exposure to HCA distinctively activates the neonatal immune system in utero with potentially long-term health consequences. Highlights: 488 differentially expressed, genes in whole blood among uninfected neonates with histologic chorioamnionitis exposure. Activation innate and adaptive immune pathways were shown and there was a potential regulatory role for microRNA miR-155. Plasma cytokines in patients with HCA exposure compared to patients without HCA included MCP-1, MPO, and MMP-9.